TOWARD UNDERSTANDING TOURIST LANDSCAPE. A COMPARATIVE STUDY OF LOCALS’ AND VISITORS’ PERCEPTION IN SELECTED DESTINATIONS IN POLAND AND GREECE - Terkenli, Theano S.; Skowronek, Ewa; Tucki, Andrzej; Kounellis, Nikolaos (Quaestiones Geographicae, 2019)
This paper critically negotiates the concept of the tourist landscape and proceeds, through a comparative cross-cultural empirical study, to test its basic conceptual premises in one upland and one seaside tourist destination, in Central Europe and in the Mediterranean. The conceptualization and employment of the term ‘tourist landscape’, in the social sciences and beyond, has been mostly intuitive and lacking a rigorous and broad-based conceptualization and empirical verification, incorporating its viewers’/users’ perceptions. On the basis of a conceptual model of the tourist landscape, the paper assesses conceptions and perceptions of the ‘tourist landscape’ and its constituent elements by tourists, locals, and tourism stakeholders in Zwierzyniec, Poland and Chios Island, Greece.